Mapping groundwater hardness in wells as a source of drinking water for the people - SOLOSSA, HERCE FARIDA; Yulfiah, Yulfiah (Institut Teknologi Adhi Tama Surabaya, 2020)
Herce Farida Solossa 20.2018.2.00117 Mapping of Groundwater Hardness Distribution of Drinking Water for Bangkalan District Community, in 2019. Thesis, Department of Environmental Engineering, Faculty of Civil Engineering and Planning, Adhi Tama Institute of Technology Surabaya, Advisor Dr. Yulfiah, ST., Msi. Water hardness is the content of certain minerals in water, generally calcium (Ca) and magnesium (Mg) ions in the form of carbonate salts and this content if it exceeds quality standards can have an impact on human health. The purpose of this study is to map the distribution of groundwater hardness as a source of water supply in Kab. Bangkalan. The sample of this study is shallow wells with a depth not exceeding 20 m. This type of research is a descriptive study with a qualitative and quantitative approach. The research sample was taken as many as 18 following the number of subdistricts in Kab. Base Samples taken are water source wells used by the community. Sampling time is the dry season. Samples taken are stored in bottles and immediately taken to the laboratory for examination. Sampling locations are made in the form of maps with the ArcGis application. The conclusion of this research is that the level of hardness in groundwater in Kab. Base has moderate value - maximum. The distribution of hard water is also evenly distributed throughout the Kab. Base with the maximum distribution from east-west to east and east-east while the hardening is starting from north and northeast to south, southwest and west. This suggestion that can be made is that residents who use shallow wells should use a filter and cook it first for drinking needs. Keywords: Mapping, hard groundwater, drinking water sourcesKeywords: Mapping, hard groundwater, drinking water sources.